Sustitución parcial de harina de trigo (triticum aestivum L) por harina de papa china (Colocasia esculenta)para la elaboración de galletas de dulce. - Trujillo Torres, Hoover Javier (2015)
The objective of this research was partially replace wheat flour potato flour Chinese (Colocasia esculenta) to make cookies fresh. This tuber is considered as a promising crop with a wide variety of applications especially in the food sector, its deficiency in gluten, it does consumable by people suffering from the condition known as celiac disease or gluten intolerance, rich in total solids between 30- 40% and up to 1% protein and 0.8 to 1% natural fibers which help clean the digestive tract.